Installation of sectional water tank / Nurul Arissa Abu Hassan - Nurul Arissa, Abu Hassan (2019)
Practical training that done under Tabung Haji Universal Builders (THUB) which is the site at the Menara Tabung Haji Ipoh. This company is function to conduct maintenance of building and known as a specialist in facilities management for all the properties that under the Tabung Haji Properties. This report is about the water storage tank. It is has the types of the tanks and their component. The installation at the Menara Tabung Haji (TH) Ipoh. The water storage tank actually change after 18 years it has been used at the TH Ipoh. Besides, this report also will having the all component that has been used for the water panel installation and all the explanation of the procedure during the tank installation at the site which is TH Ipoh